Comparison of TR Band™ and VasoStat™ Hemostasis Devices following Transpedal Catheterization for Lower Extremity Revascularization for Peripheral Arterial Disease. (30th June 2016) - Kwan, Tak W.; Patel, Apurva; Parikh, Roosha; Auguste, Uschi; Rosero, Hugo; Huang, Yili; Liou, Michael; Ratcliffe, Justin; Puma, Joseph
Abstract : Background: Transpedal access is increasingly utilized for peripheral vascular catheterization. There is a paucity of data on the use of radial hemostasis devices as an alternative to manual compression for achievement of hemostasis after this approach. Objective: To compare safety and efficacy of two hemostasis devices following transpedal catheterization for lower extremity revascularization for peripheral arterial disease. Methods: A consecutive cohort of patients with bilateral Rutherford 2–5 disease who underwent transpedal catheterization for peripheral vascular interventions were retrospectively analyzed. In each patient, retrograde tibial artery access was obtained, a 4 French sheath was placed, and all revascularization was performed via tibial access. In all patients, a TR Band™ (Terumo Medical, n = 215) and/or VasoStat™ (Forge Medical, n = 99) were used to apply puncture site compression, following removal of the tibial sheath until hemostasis was achieved. Safety and efficacy of each device was compared. Results: Puncture site hemostasis was achieved in all patients within 2 hours of sheath removal facilitating early discharge. Two access site pseudoaneurysms occurred within 30 days of revascularization, one of which followed TR Band™ placement and the other following VasoStat™ placement (P = 0.53). Each patient was successfully treated with ultrasound‐guided thrombin injection. Loss of access site patency by duplex ultrasound occurred in 2 patients following the TR Band™ and a single patient following the VasoStat™ (P = 1.0). Conclusion: Both the TR Band™ and the VasoStat™ were effective in achieving hemostasis following transpedal catheterization with low rates of complications.